Do hyperparasitoids disrupt the biological control of Pseudococcus longispinus in persimmon? - Plata, Ángel; Gómez-Martínez, María A.; Beitia, Francisco J.; Tena, Alejandro (Elsevier, 2024)
The long-tailed mealybug, Pseudococcus longispinus, represents a threat for several crops worldwide and has become the main pest of Mediterranean persimmon. Parasitoids are the primary natural enemies of P. longispinus, but their efficacy is highly variable among crops and countries. Here, we tested whether hyperparasitoids hinder the biological control of P. longispinus in Mediterranean persimmon. For this aim, we sampled 16 orchards across two consecutive years and measured the impact of primary parasitoids and hyperparasitoids on P. longispinus. Anagyrus fusciventris was the most abundant and widely distributed primary parasitoid. Population growth rate of the mealybug became negative when parasitism was higher than 30%. The hyperparasitoids Chartocerus sp. and Prochiloneurus sp. emerged mostly from large mealybug mummies that were used by A. fusciventris females. However, and contrary to our hypothesis, hyperparasitism did not affect the population growth rate of P. longispinus within the same year, suggesting that the high abundance of hyperparasitoids did not disrupt the biological control of this invasive mealybug. Based on these results, we propose several strategies based on conservation and augmentative biological control to improve the management of P. longispinus in persimmon.